2020
DOI: 10.1080/10426507.2020.1804151
|View full text |Cite
|
Sign up to set email alerts
|

Two possible ways to combine boron and gadolinium for Gd-guided BNCT. A concept

Abstract: Two ways of synthesis of theragnostic compounds for Gd-guided boron neutron capture therapy of cancer are proposed. The first way is based on modification of DO3A ligand, which a capable to form stable complexes with gadolinium, with attachment of boron-containing moieties and additional functional groups which can be used for conjugation with various biomacromolecules. The second way is based on the introduction of additional chelating groups into a boron-containing moiety-carborane-based ligand. It is expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…To the best of our knowledge, there is only one communication in the literature on the synthesis of the gadolinium dicarbollide complex [3,3-(THF) 2 -3,3′-Gd(1,2-C 2 B 9 H 11 ) 2 ] − [ 30 ], however, its characterization is not sufficient to be reliable. At the same time, a careful analysis of the literature on dicarbollide complexes of other lanthanides showed that complexes of this type are usually unstable due to loss of solvent molecules, however their stability can be increased by using carborane ligands with substituents containing pendant donor groups [ 31 ]. In this case, the donor groups take the place of easily removable molecules of the coordinated solvent, which leads to an increase in the complex stability due to the chelate effect.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, there is only one communication in the literature on the synthesis of the gadolinium dicarbollide complex [3,3-(THF) 2 -3,3′-Gd(1,2-C 2 B 9 H 11 ) 2 ] − [ 30 ], however, its characterization is not sufficient to be reliable. At the same time, a careful analysis of the literature on dicarbollide complexes of other lanthanides showed that complexes of this type are usually unstable due to loss of solvent molecules, however their stability can be increased by using carborane ligands with substituents containing pendant donor groups [ 31 ]. In this case, the donor groups take the place of easily removable molecules of the coordinated solvent, which leads to an increase in the complex stability due to the chelate effect.…”
Section: Resultsmentioning
confidence: 99%
“…The researchers incorporated Gd-DTPA complexes on the silica layer surfaces of this nanoparticle, so that it could also well-behave in the MR imaging and exploit the therapeutic effects of GdBNCT at the same time 92 . One other related study showed several means of combination of 10 B and 157 Gd which can be used in Gd-guided BNCT, which pointed out that there are mainly two synthesis modes of this dual element agent, one was based on DOTA chelators and the other one was based on the structure of carborane cages 93 . Different approaches to chemical synthesis could figure out the stability and toxicity of various types of these compounds.…”
Section: B-gd Binary Nanomedicinementioning
confidence: 99%
“…Anufriev等人 [51] 提出了设计Gd-B双携带剂的两个 方案: 一是修饰多胺多羧酸类配体, 一端螯合钆, 一端 连接含硼基团, 并增加与各种生物大分子结合的官能 团; 二是在碳硼烷上连接可与钆螯合的基团. Matsu-mura等人 [52] 最早开展了Gd-B双携带剂的研究.…”
Section: Gd-b双携带剂unclassified